Reflexões sobre o humanismo antigo - Schüler, Donaldo (Classica - Revista Brasileira de Estudos Clássicos, 1993)
We don't possess any clear idea about man', dectared Max Scheler at the beginning of our century. With the investigations made after him, the concepts about man became even mote obscure. The aim of this essay is to invetigate the efforts made to understand man in Ancient Greece, beginning with Heraclitus and ending with Diogenes. For this purpose lyric poetry, tragedy and philosophical texts are analysed.